Increased transfer of trace metals and Vibrio sp. from biodegradable microplastics to catfish Clarias gariepinus. (1st April 2022) - Jang, Faddrine Holt; Wong, Changi; Choo, Jenny; Aun Sia, Edwin Sien; Mujahid, Aazani; Müller, Moritz
Abstract: Microplastic ingestion has been documented in various aquatic species. This causes physical damage, and additionally contaminated microplastics transfer attached pollutants and microbial pathogens to ingesting organisms. Continued metal accumulation can lead to toxicity and adverse health effects; attached microbial pathogens can cause dysbiosis - which lowers host immunity and promotes infections. Catfish, Clarias gariepinus, are a major food source in Southeast Asia, a hotspot of plastic pollution. This study aimed to quantify the transfer of the trace metals copper (Cu) and lead (Pb) -at environmentally relevant concentrations-from microplastics (polyamide 12, PA12, and polylactic acid, PLA) to catfish. Fish were reared for three months and exposed to seven different combinations of feed, supplemented with plastics and metals. At monthly intervals, fish gills, intestines, liver, and edible muscles were analysed for Cu and Pb concentrations using ICP-OES, and the intestines content assessed for Vibrio sp.. Our results showed that biodegradable PLA transferred higher amounts of metals to catfish than expected and also led to increased Vibrio counts in the intestines compared to PA12. Trace metal accumulation was significantly different in varying tissues, with highest concentrations observed in the gills, followed by liver, intestines, and lastly edible muscles. The results of this study further support the existing evidence that microplastics act as efficient shuttles to concentrate and transfer metals. They also indicate that their uptake can cause dysbiosis (increased numbers of Vibrio sp.). Most importantly, however, our study highlights that biodegradable polymers, such as PLA, could actually pose a greater environmental threat when ingested compared to the more common polymers such as PA12. Graphical abstract: Image 1 Highlights: Trace metals and bacteria attach to microplastic surfaces. Microplastics act as efficient shuttles to concentrate and transfer metals to catfish. Biodegradable microplastic transferred higher metal concentrations. Biodegradable microplastic caused increased Vibrio counts in catfish intestine. Biodegradable polymers could actually pose a greater environmental threat upon ingestion.